1992
DOI: 10.1523/jneurosci.12-02-00607.1992
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of EPSP-spike (E-S) potentiation in hippocampal CA1 pyramidal cells

Abstract: Long-term potentiation of hippocampal excitatory synapses is often accompanied by an increase in the probability of spiking to an EPSP of fixed strength (E-S potentiation). We used computer simulations of a CA1 pyramidal neuron to test the plausibility of the hypothesis that E-S potentiation is caused by changes in dendritic excitability. These changes were simulated by adding "hot spots" of noninactivating voltage-sensitive Ca2+ conductance to various dendritic compartments. This typically caused spiking in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…We show here that changes in excitability accompany modifications in synaptic efficacy and therefore follow the Bienenstock, Cooper, and Munrow rule (29). E-S P and E-S depotentiation were found to be specific to the stimulated pathway, suggesting that the underlying changes in intrinsic excitability are probably restricted to the active dendritic area (30). Thus, the input specificity conferred by synaptic efficacy is respected and the functional contrast between active and inactive synaptic inputs is not subsequently altered by modifications in the intrinsic excitability.…”
Section: Discussionsupporting
confidence: 56%
“…We show here that changes in excitability accompany modifications in synaptic efficacy and therefore follow the Bienenstock, Cooper, and Munrow rule (29). E-S P and E-S depotentiation were found to be specific to the stimulated pathway, suggesting that the underlying changes in intrinsic excitability are probably restricted to the active dendritic area (30). Thus, the input specificity conferred by synaptic efficacy is respected and the functional contrast between active and inactive synaptic inputs is not subsequently altered by modifications in the intrinsic excitability.…”
Section: Discussionsupporting
confidence: 56%
“…In preliminary experiments of this kind (S. Chattarji, unpublished data ; see also ref 36) tetanization of a proximal input to CAI neurons causes potentiation of the population spikes elicited through both the tetanized input and a distal untetanized input, in agreement with the prediction . Recently evidence of a nonspecific component of LTP in CAI neurons has also been reported (37) but it cannot be seen if the tetanized and untetanized inputs are segregated to basal and apical dendrites, respectively, consistent with the simulation results of Figure 9C .…”
Section: Examplessupporting
confidence: 76%
“…does not change ( Figure 8A We used a model to investigate some of the consequences of the hypothesis that E-S potentiation is caused by an increase in postsynaptic excitability . 11 The cellular morphology used in these simulations was identical to that in Figure 2 . The axon and soma were excitable but the dendrites were initially passive .…”
Section: Examplesmentioning
confidence: 99%
“…In CA1 hippocampal pyramidal neurons, after induction of LTP, postsynaptic spike firing increases more than would be expected from synaptic LTP, a phenomenon referred to as EPSP-to-spike (E-S) potentiation (Bliss and Lomo, 1973;Andersen et al, 1980). E-S potentiation has been reported to depend on disinhibition (Abraham et al, 1987;Chavez-Noriega et al, 1990), but later studies have suggested a change in the intrinsic excitability (Wathey et al, 1992;Pugliese et al, 1994;Jester et al, 1995;Wang et al, 2003). More recent studies suggest that full expression of E-S potentiation requires both GABA A receptor-mediated disinhibition and intrinsic potentiation (Daoudal et al, 2002;Staff and Spruston, 2003).…”
Section: Introductionmentioning
confidence: 99%